(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study was to develop and evaluate a cervical cancer prevention program for Vietnamese married immigrant women who show the high incidence of cervical cancer. In this regard, this study presents the grounds for the cervical cancer prevention program to be spread and adopted widely to promote Vietnamese married immigrant women’s reproductive health. Method/Statistical Analysis: Program was developed by the ADDIE model. The developed program was applied to Vietnamese immigrant women. Study design is random control group pre-test, post-test design. The effects of the program were assessed by health belief of Pap testing, knowledge of cervical cancer, and intention of preventive behavior. In the experimental group, four 120-minutes sessions of cervical cancer prevention education program intervention were provided once a week. Findings: The results indicate that the educational program to prevent cervical cancer helps Vietnamese married immigrant women to lower the perceived barriers in cervical cancer prevention, to enhance the awareness about cervical cancer, and to raise the intention for cervical cancer prevention behavior, which proves the prevention program is very effective and useful. Improvements/Applications: We expect that the devised program in this study be widely used in multi-cultural family support center to promote Vietnamese married immigrant women’s reproductive health and quality of life.